The factors that contribute to the significant growth towards demand for health insurance / Nur Azmira Kamsin - Kamsin, Nur Azmira (2015)
Health insurance is a demanding program designed to covers surgical and medical expenses that are incurred by the insured. The objective of this research is to determine the factors that contribute to the significant growth towards demand for health insurance and to identify what are the major factors that contribute to the significant towards demand for health insurance. The factors that influence customer to purchase insurance are the income level and education level. all the respondents are insurance customer from specified area and they experience in using the service from their insurance provider. The study will be gather using 50 set of questionnaires as it will distributed at Klang valley. This research was conducted using various methods such as “Reliability Test, Descriptive Statistics and Multiple Regression”. The result of the findings indicated that income level is the major factor that will influence demand towards health insurance compared to another two factors which are age level and education level. In conclusion, all the objectives have successfully been met. Some recommendations have been suggested in order to improving the demand of health insurance.